The Multifaceted Nature of Exploration and Exploitation: Value of Supply, Demand, and Spatial Search for Innovation - Sidhu, Jatinder S.; Commandeur, Harry R.; Volberda, Henk W. (Organization Science, 2007)
In this paper, exploration and exploitation are conceptualized in terms of a nonlocal-local search continuum in three-dimensional supply, demand, and geographic space. Using cross-sectional data from a wide range of manufacturing industries, we develop and validate an operational measure of the exploration-exploitation concept. In line with theory-based arguments, our analysis suggests that the value of supply-side, demand-side, and spatial exploration and exploitation is contingent on the environment. While boundary-spanning supply-side search is found to be positively associated with innovation in more-dynamic environments typical of the entrepreneurial regime phase of technology evolution, such exploration appears to hurt innovation in less-dynamic environments. In a reverse fashion, while boundary-spanning demand-side search is found to be favorably associated with innovation in less-dynamic environments, it appears to harm innovation in a more-dynamic context. Interestingly, spatial boundary-spanning search seems to contribute to innovation in more- as well as less-dynamic environments. With the caveat that the substantive findings of this study are based on cross-sectional data, we discuss the implications of our work and future research directions.